Casting technology: sustainable metal forming process - Sulaiman, Shamsuddin (Universiti Putra Malaysia Press, 2015)
Metal casting is a process where molten metal is poured by gravity or injected with pressure into a mould cavity to produce the desired product. Most cast products are in finished goods form, which require minimal level of machining and surface finishing to achieve the desired tolerance and surface quality. Many industrial parts and components are produced by the method of casting, including engine blocks, crankshafts, automotive components, railroad equipment, plumbing fixtures, power tools, very large components for hydraulic turbines and so on. In terms of the theoretical application, two pertinent parameters, i.e. flow and thermal aspects, are explained in detail. The advancement from conventional to advanced materials has pushed casting technology into a competitive environment based on product requirements. Further, Computer Aided Design and Computer Aided Manufacturing (CAD/CAM) together with machine technology have also been introduced to the foundry or casting industry. This lecture will cover the development of Advanced Manufacturing Technology (AMT) applied in metal casting processes. Selected works on casting processes and technology for conventional and advanced materials are reviewed, and studies on metal matrix composites for engineering products are discussed. Other than process simulation technology, advances in mould and die design technology are also being applied in casting product development. With these technologies, the casting process will be maintained and sustained as an important and relevant component of the metal forming process.